2013
DOI: 10.1371/journal.pone.0051642
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure and Calpain-10 Polymorphisms Impair the Function of Pancreatic Beta-Cells in Humans: A Pilot Study of Risk Factors for T2DM

Abstract: The incidence of type 2 diabetes mellitus (T2DM) is increasing worldwide and diverse environmental and genetic risk factors are well recognized. Single nucleotide polymorphisms (SNPs) in the calpain-10 gene (CAPN-10), which encodes a protein involved in the secretion and action of insulin, and chronic exposure to inorganic arsenic (iAs) through drinking water have been independently associated with an increase in the risk for T2DM. In the present work we evaluated if CAPN-10 SNPs and iAs exposure jointly contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 51 publications
(107 reference statements)
1
28
0
1
Order By: Relevance
“…In the db/db mouse model of T2D in which a defect in the leptin receptor promotes the development of obesity and diabetes, exposure to arsenic through drinking water enhanced the development of hyperglycemia with concomitant reductions in insulin levels, suggesting an arsenic-induced impairment in β-cell function [477]. The non-obese diabetic (NOD) mouse, in contrast, is a model of type 1 diabetes as these mice develop autoimmune inflammation of the pancreatic islets (insulitis) and insulinopenic diabetes.…”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…In the db/db mouse model of T2D in which a defect in the leptin receptor promotes the development of obesity and diabetes, exposure to arsenic through drinking water enhanced the development of hyperglycemia with concomitant reductions in insulin levels, suggesting an arsenic-induced impairment in β-cell function [477]. The non-obese diabetic (NOD) mouse, in contrast, is a model of type 1 diabetes as these mice develop autoimmune inflammation of the pancreatic islets (insulitis) and insulinopenic diabetes.…”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…High expression of miR-221/222 in breast cancer tissues causes insulin resistance and increases the metabolic load on pancreatic β cells. This leads to elevated blood glucose levels, and T2DM finally occurs when compensation becomes insufficient (Díaz-Villaseñor et al, 2013). Therefore, miR-221/222 and estrogen may jointly participate in pathogenesis of T2DM with post-menopausal breast cancer in overweight or obese females.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of arsenic-exposed populations have found that higher inorganic arsenic and MAs in urothelial cells and higher DMAs in urine are more strongly associated with DM than drinking water measures of arsenic or U-tAs [44,59,[61][62]. These differences in arsenic metabolite profiles represent a potential indicator of the risk of developing DM and could be mediated by differences in genotypes, specifically single nucleotide polymorphisms (SNPs), of critical genes such as AS3MT [63], CAPN-10 -a calcium-dependent protease that plays a key role in exocytosis of insulin-containing vesicles in β-cells [64], GSTO1 -an enzyme that contributes to the reduction of arsenic from the pentava-future science group Arsenic-associated diabetes & the epigenome Special Report lent to trivalent form [57] and NOTCH2 -a member of a signaling cascade involved in cell differentiation [57][58][64][65]. Interestingly, the majority of SNPs associated with differences in arsenic metabolism occur in noncoding regions of the genes, suggesting a potential role for regulatory factors or splice variants.…”
Section: Genetic and Epigenetic Underpinnings For Arsenic-associated Dmmentioning
confidence: 99%